Use of Living Strategies among Adults Aging with HIV in Canada: Comparison by Age-Group Using Data from the HIV, Health and Rehabilitation Survey. (9th May 2018) - O'Brien, Kelly Kathleen; Dagenais, Matthieu; Solomon, Patricia; Worthington, Catherine; Chan Carusone, Soo; Ibáñez-Carrasco, Francisco; Hanna, Steven; Gahagan, Jacqueline; Baxter, Larry; Robinson, Gregory; Gayle, Patriic; James, Dawn; et al.
Objective: To examine the type and frequency of living strategies used by adults living with HIV. Methods: We conducted a cross-sectional web-based survey that included 51 living strategies: maintaining sense of control, attitudes and beliefs, blocking HIV out of the mind, and social interaction. We examined the frequency of use and compared the proportion of respondents who engaged in strategies across 3 age-groups (<40 years, 40-49 years, and ≥50 years). Results: Of the 935 participants, the majority were men (79%) and most (≥60%) engaged "most" or "all of the time" in healthy lifestyle strategies and maintained a positive outlook living with HIV. Compared to younger participants, a higher proportion of older adults (≥50 years) engaged "most" or "all the time" in strategies that involved maintaining control over health and adopting positive attitudes and outlook living with HIV. Conclusions: Findings can help to inform the role of self-management to enhance successful aging with HIV.